Enhanced Potency and Durability of Antibody Response to Seasonal Trivalent Inactivated Influenza Vaccine (TIV) Combined with a Novel Water-in-Oil Adjuvant System at Reduced Hemagglutinin (HA) Doses. (4th October 2017) - Gorse, Geoffrey J; Grimes, Stephen; Buck, Helen; Mulla, Hussain; White, Peter; Graham, Irene; Treanor, John J; Hill, Heather; May, Jeanine; Blackburn, Peter
Abstract: Background: New influenza vaccines are needed to increase vaccine efficacy against infection and illness. Adjuvants may allow HA dose-sparing while increasing the antibody response. MAS-1 is an investigational low viscosity, free-flowing, water-in-oil emulsion-based adjuvant delivery system with stable nanoglobular droplets whether manufactured in bulk or at point-of-use (POU). MAS-1 oily vehicle is stable for at least 5 years at room temperature, in bulk or POU vials. Methods: A phase 1, double-blind, single-center, safety and immunogenicity, HA dose escalation trial was conducted. 1, 3, 5 or 9 µg per HA from the licensed 2014/15 seasonal TIV prepared POU with a fixed dose of MAS-1 adjuvant in 0.3 mL emulsion compared with standard dose (SD, 15 µg per HA) TIV in 0.5 mL was injected IM on day 1. Safety was measured by reactogenicity, adverse events, and safety labs. Serum hemagglutination inhibition (HAI) antibody titers were measured at 5 time points post-vaccination. Results: 72 subjects, age 18–47 years, were randomly assigned to either adjuvanted vaccine or TIV in a 2:1 ratio. The 1 and 3 µg per HA cohorts were enrolled together, then the 5 µg follo wed by the 9 µg per HA cohorts. Common injection site reactions were mild tenderness (74%) and pain (54%), resolving by 5 days post-vaccination. Common systemic reactions were mild headache (36%), myalgia (19%), malaise (18%) and fatigue (18%) through day 14 post-vaccination. Safety labs were not concerning. Geometric mean antibody titers against component strains were higher, of longer duration and peaked later in the adjuvanted vaccine groups than with SD TIV (Figures 1 – 3). Seroconversion rates (%) had a similar pattern: Conclusion: MAS-1 adjuvant provided HA dose-sparing without significant systemic or local safety concerns, higher HAI antibody titers and seroconversion rates for a longer duration than SD TIV, and could conceivably contribute to greater vaccine efficacy. Disclosures: G. J. Gorse, Nova Immunotherapeutics Limited: Principal Investigator at Saint Louis University, Funding to Saint Louis University for the clinical study; S. Grimes, Mercia Pharma, Inc.: Employee and Principal Scientist, Salary; H. Buck, Nova Immunotherapeutics Limited: Consultant, Consulting fee; H. Mulla, Nova Immunotherapeutics Limited: Employee, Salary; P. White, Nova Immunotherapeutics Limited: Employee, Salary; Mercia Pharma, Inc.: Shareholder, Licensing agreement or royalty; P. Blackburn, Mercia Pharma, Inc.: President and CSO, Salary